A study of individual and interaction effect of process parameters on friction welded AISI 410 and AISI 430 joint. (2021) - Senthilkumar, G.; Ramakrishnan, R.
Highlights: We address the study on friction welding of AISI 410 and AISI 430 Materials. The significance of each process parameters was predicted. The interaction effects of parameters were studied in detailed manner. The results will offer a database for friction welding of AISI 410 and AISI 430. Abstract: Permanent fastening of metals is a good technique in mechanical industries since bronze age and now it is an attainable gradual improvement gave a surge to modern welding development. The selection of welding technique and its parameters are king pin to produce defects free joint and more productivity. In this study continuous drive solid state friction welding is selected for joining AISI 410 and AISI 430 materials. Taguchi analysis is used to predict the optimal level of parameters and ANOVA is used to find out individual and interactive effects of parameters. L12 OA is selected to carry out experiments with 4 process parameters and 2 levels each. The responses measured are tensile strength and axial shortening. The contribution of process parameters to get tensile strength are friction pressure, rotational speed, forging pressure and combined effect of friction pressure & forging pressure are 34.87%, 28.59%, 17.7% and 15.07% respectively. Therefore, this paper is a window for friction welding research of two different ferrous materials joint properties considering the effect of individual and interaction factors.